2013
DOI: 10.1080/19443994.2013.792136
|View full text |Cite
|
Sign up to set email alerts
|

Solar photo-Fenton treatment of petroleum extraction wastewater

Abstract: A B S T R A C TThe purpose of this study is to investigate the treatment of petroleum-extraction wastewater by means of a photo-Fenton like process using sunlight as irradiation source. According to the experimental results, a reduction of the wastewater UV absorption spectral intensity indicates that polycyclic aromatic hydrocarbons and aromaticity removal of approximately 92.7 and 96.2%, respectively, were obtained after 7 h of sunlight exposure using 485.3 mmol L À1 of hydrogen peroxide. For the investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 25 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…Da Rocha et al, (2013) showed that polycyclic aromatic hydrocarbons and aromaticity removal of approximately 92.7 and 96.2%, respectively, from petroleum-extraction wastewater were obtained by a solar photo-Fenton like process after 420 min and solar photo-Fenton process achieved 53% COD removal. Tony et al, (2012) obtained 50% COD removal after using (H2O2/ Fe +2 /UV) method under optimal conditions; pH 3, H2O2/Fe +2 ratio 10 while the current study revealed that the solar photo-Fenton process in an AOP was more efficient in the petroleum wastewater treatment, achieving a 74.7% COD removal at conditions; pH 3.68, H2O2/ Fe +2 ratio 14.…”
Section: Comparison the Results With Other Workmentioning
confidence: 99%
“…Da Rocha et al, (2013) showed that polycyclic aromatic hydrocarbons and aromaticity removal of approximately 92.7 and 96.2%, respectively, from petroleum-extraction wastewater were obtained by a solar photo-Fenton like process after 420 min and solar photo-Fenton process achieved 53% COD removal. Tony et al, (2012) obtained 50% COD removal after using (H2O2/ Fe +2 /UV) method under optimal conditions; pH 3, H2O2/Fe +2 ratio 10 while the current study revealed that the solar photo-Fenton process in an AOP was more efficient in the petroleum wastewater treatment, achieving a 74.7% COD removal at conditions; pH 3.68, H2O2/ Fe +2 ratio 14.…”
Section: Comparison the Results With Other Workmentioning
confidence: 99%
“…(2014) [1][2][3][4][5][6][7][8][9] www.deswater.com doi: 10.1080/19443994.2014.951968 (the unit in which a device designed to separate gross amounts of oil from the wastewater effluents of oil refineries), effluents of this refinery contain large amounts of hydrogen sulfide and petroleum hydrocarbons dissolved in water.…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…Many organic contaminants absorb UV energy in the range of 200-300 nm and decompose due to direct photolysis or become excited and more reactive with chemical oxidants like hydrogen peroxide and ozone. Ozone readily absorbs UV radiation at 254 nm wavelength producing H 2 O 2 as an intermediate, which then decomposes to Å OH (Reactions (6) and (7)) [2,17].…”
Section: Effects Of Uv Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…Davarnejad et al (2015) showed that maximum COD removal was around 82.55% at H2O2/PRW (Ratio of a mole of H2O2 per petroleum refinery wastewater volume) of 0.04, H2O2/Fe 2+ molar ratio of 2.75, pH of 3.5 and reaction time of 90 min. Da Rocha et al, (2013) showed that the 53% COD removal was achieved by the solar photo-Fenton process from petroleum wastewater.…”
Section: Fenton Photo-fenton and Fenton-like Processesmentioning
confidence: 99%